CHD1L promotes lineage reversion of hepatocellular carcinoma through opening chromatin for key developmental transcription factors. Issue 5 (4th March 2016) - Liu, Ming; Chen, Leilei; Ma, Ning‐Fang; Chow, Raymond Kwok Kei; Li, Yan; Song, Yangyang; Chan, Tim Hon Man; Fang, Shuo; Yang, Xiaodong; Xi, Shaoyan; Jiang, Lingxi; Li, Yun; et al.
Abstract : High‐grade tumors with poor differentiation usually show phenotypic resemblance to their developmental ancestral cells. Cancer cells that gain lineage precursor cell properties usually hijack developmental signaling pathways to promote tumor malignant progression. However, the molecular mechanisms underlying this process remain unclear. In this study, the chromatin remodeler chromodomain‐helicase‐DNA‐binding‐protein 1‐like (CHD1L) was found closely associated with liver development and hepatocellular carcinoma (HCC) tumor differentiation. Expression of CHD1L decreased during hepatocyte maturation and increased progressively from well‐differentiated HCCs to poorly differentiated HCCs. Chromatin immunoprecipitation followed by high‐throughput deep sequencing found that CHD1L could bind to the genomic sequences of genes related to development. Bioinformatics‐aided network analysis indicated that CHD1L‐binding targets might form networks associated with developmental transcription factor activation and histone modification. Overexpression of CHD1L conferred ancestral precursor‐like properties of HCC cells both in vitro and in vivo . Inhibition of CHD1L reversed tumor differentiation and sensitized HCC cells to sorafenib treatment. Mechanism studies revealed that overexpression of CHD1L could maintain an active "open chromatin" configuration at promoter regions of estrogen‐related receptor‐beta and transcription factor 4, both of which are important regulators of HCC self‐renewal and differentiation. In addition, we found a significant correlation of CHD1L with developmental transcriptional factors and lineage differentiation markers in clinical HCC patients. Conclusion: Genomic amplification of chromatin remodeler CHD1L might drive dedifferentiation of HCC toward an ancestral lineage through opening chromatin for key developmental transcriptional factors; further inhibition of CHD1L might "downgrade" poorly differentiated HCCs and provide novel therapeutic strategies. (Hepatology 2016;63:1544‐1559)